Adapting a standardised international 24 h dietary recall methodology (GloboDiet software) for research and dietary surveillance in Korea. Issue 11 (22nd April 2015) - Park, Min Kyung; Park, Jin Young; Nicolas, Geneviève; Paik, Hee Young; Kim, Jeongseon; Slimani, Nadia
Abstract : During the past decades, a rapid nutritional transition has been observed along with economic growth in the Republic of Korea. Since this dramatic change in diet has been frequently associated with cancer and other non-communicable diseases, dietary monitoring is essential to understand the association. Benefiting from pre-existing standardised dietary methodologies, the present study aimed to evaluate the feasibility and describe the development of a Korean version of the international computerised 24 h dietary recall method (GloboDiet software) and its complementary tools, developed at the International Agency for Research on Cancer (IARC), WHO. Following established international Standard Operating Procedures and guidelines, about seventy common and country-specific databases on foods, recipes, dietary supplements, quantification methods and coefficients were customised and translated. The main results of the present study highlight the specific adaptations made to adapt the GloboDiet software for research and dietary surveillance in Korea. New (sub-) subgroups were added into the existing common food classification, and new descriptors were added to the facets to classify and describe specific Korean foods. Quantification methods were critically evaluated and adapted considering the foods and food packages available in the Korean market. Furthermore, a picture book of foods/dishes was prepared including new pictures and food portion sizes relevant to Korean diet. The development of the Korean version of GloboDiet demonstrated that it was possible to adapt the IARC-WHO international dietary tool to an Asian context without compromising its concept of standardisation and software structure. It, thus, confirms that this international dietary methodology, used so far only in Europe, is flexible and robust enough to be customised for other regions worldwide.